2019
DOI: 10.3390/pathogens8040300
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic Pathway of Feline Coronavirus for Cell Entry: Differences in Serotype-Dependent Viral Entry Pathway

Abstract: Feline coronavirus (FCoV) is a pathogen causing a lethal infectious disease in cats, feline infectious peritonitis. It has two serotypes (type I FCoV and type II FCoV). According to our previous study, type I FCoV infection is inhibited by compounds inducing intracellular cholesterol accumulation, whereas type II FCoV infection is not inhibited. Intracellular cholesterol accumulation was reported to disrupt late endosome function. Based on these findings, types I and II FCoV are considered to enter the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
0
17
0
5
Order By: Relevance
“…The oxysterol 25-hydroxycholesterol is a metabolite of cholesterol that is produced and secreted by macrophages and has multiple effects on lipid metabolism, especially lipid biosynthesis and immunity [ 63 ]. 25-hydroxycholetserol has been shown to inhibit feline coronavirus, porcine epidemic diarrhea virus, and porcine transmissible gastroenteritis virus possibly through induction of intracellular cholesterol accumulation [ 64 , 65 ]. Moreover, 25-hydroxycholesterol is active against various emerging RNA viruses, including Ebola virus, Nipah virus, Rift Valley fever virus, and Zika virus, and DNA and RNA viruses that cause chronic infections, such as human immunodeficiency virus, herpes simplex virus, and varicella zoster virus [ 18 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oxysterol 25-hydroxycholesterol is a metabolite of cholesterol that is produced and secreted by macrophages and has multiple effects on lipid metabolism, especially lipid biosynthesis and immunity [ 63 ]. 25-hydroxycholetserol has been shown to inhibit feline coronavirus, porcine epidemic diarrhea virus, and porcine transmissible gastroenteritis virus possibly through induction of intracellular cholesterol accumulation [ 64 , 65 ]. Moreover, 25-hydroxycholesterol is active against various emerging RNA viruses, including Ebola virus, Nipah virus, Rift Valley fever virus, and Zika virus, and DNA and RNA viruses that cause chronic infections, such as human immunodeficiency virus, herpes simplex virus, and varicella zoster virus [ 18 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, available NPC1 inhibitors U1866A and imipramine inhibited several enveloped viruses including MERS-CoV and SARS-CoV ( Wrensch et al, 2014 ), Ebola ( Herbert et al, 2015 ; Lu et al, 2015 ), HIV-1 ( Tang et al, 2009 ), HCV ( Elgner et al, 2016 ), influenza A ( Eckert et al, 2014 ), and chikungunya ( Wichit et al, 2017 ) by de-acidifying endolysosomes and increasing lipid accumulation ( Lange et al, 2012 ) ( Figure 2 ). Also, the anti-fungal drugs itraconazole and posaconazole are not only inhibitors of NPC but also have antiviral activity ( Strating et al, 2015 ; Trinh et al, 2017 ; Meutiawati et al, 2018 ; Rhoden et al, 2018 ; Schloer et al, 2019 ; Takano et al, 2019a ; Takano et al, 2019b ). In addition, cepharanthine, an inhibitor of TPC2 and NPC1, has antiviral activity ( Figure 2 ) ( Zhang et al, 2005 ; Matsuda et al, 2014 ; Lyu et al, 2017 ; Bailly, 2019 ; Kim et al, 2019 ; Fan et al, 2020 ; Rogosnitzky et al, 2020 ).…”
Section: Effects Of Endolysosome Ph On Coronavirus Infectionmentioning
confidence: 99%
“…We consider these drugs to be a treatment option until antiviral drugs such as GC-376 and GS-441524 become available. In addition, these antiviral drugs exert therapeutic effects on FIP by mechanisms different from those of ADA and ICZ [16,18,21,23]. In the future, the evaluation of the therapeutic effects of their concomitant use may aid in the development of more-effective treatments for FIP.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs have been confirmed to reduce the proliferation of FIPV, but they are not commercially distributed as veterinary drugs. We previously found that itraconazole (ICZ), which is used in veterinary medicine, reduces the proliferation of type I FIPV [21][22][23]. However, the therapeutic effects of ICZ in cats with FIP remain unclear.…”
Section: Introductionmentioning
confidence: 99%